2016
DOI: 10.15412/j.bcn.03070201
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolic Antioxidants and Neuronal Regeneration

Abstract: Many studies indicate that oxidative stress is involved in the pathophysiology of neurodegenerative diseases. Oxidative stress can induce neuronal damages, modulate intracellular signaling and ultimately leads to neuronal death by apoptosis or necrosis. To review antioxidants preventive effects on oxidative stress and neurodegenerative diseases we accumulated data from international medical journals and academic informations’ sites. According to many studies, antioxidants could reduce toxic neuronal damages an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 49 publications
0
43
0
1
Order By: Relevance
“…The anti glycation activity demonstrated by HAEF indicates that MD-1 supplementation may control the development of associated micro vascular complications in diabetes patients. Literature reports on the glycation protective effect of antioxidants such as vitamin C, poly phenols and flavonoids [37] endorsed the observed activity of the polyphenol rich HAEF in anti oxidant activity, thereby also substantiating its effect on AGEs formation.…”
Section: Discussionmentioning
confidence: 89%
“…The anti glycation activity demonstrated by HAEF indicates that MD-1 supplementation may control the development of associated micro vascular complications in diabetes patients. Literature reports on the glycation protective effect of antioxidants such as vitamin C, poly phenols and flavonoids [37] endorsed the observed activity of the polyphenol rich HAEF in anti oxidant activity, thereby also substantiating its effect on AGEs formation.…”
Section: Discussionmentioning
confidence: 89%
“…Both in vivo and in vitro experiments have demonstrated the neuroprotective effects of curcumin. For instance, curcumin can protect against neurodegenerative conditions such as Alzheimer's disease (AD), Parkinson's disease (PD), Huntington's disease (HD), and focal cerebral ischemia by attenuating neuronal apoptosis and inducing neuronal differentiation . Recently, some reports have revealed that curcumin could stimulate proliferation of neural progenitor cells (NPCs) and adult hippocampal neurogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, curcumin has been widely used in cancer chemoprevention and tumor growth suppression studies. 3 and focal cerebral ischemia 4 by attenuating neuronal apoptosis and inducing neuronal differentiation. [5][6][7] Recently, some reports have revealed 8,9 that curcumin could stimulate proliferation of neural progenitor cells (NPCs) and adult hippocampal neurogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of evidence suggests that polyphenols and lavonoids scavenge RNS and ROS, thus playing an important bene icial role in patients suffering from degenerative diseases related to aging [95][96][97]. Polyphenols are key antioxidant substances found in abundant quantities in various fruits, such as grapes, blueberries, and tomatoes, vegetables, olive oil, spices, herbs, and certain beverages such as tea and coffee [95,96,98,99]. In AD, polyphenols may reduce the levels of Aβ [95,96].…”
Section: Alzheimer's Disease and Nutrientsmentioning
confidence: 99%